Road Sickness: The Case of Oliver Stone’s Natural Born Killers - Fraser, Ryan (Cinémas)

(untitled) (Cinémas, 2008)
AbstractThe “violent” road movie is unique in the panoply of the genre. Under discussion here is Oliver Stone’s controversial Natural Born Killers (1994), a piece that the director has described as a commentary on violence as the American social ill. Using this notion of illness, of organic pathology, as a central thematic node, the article proceeds to examine the violent modes of cultural mobility present in the film’s themes, its narrative arc and finally, in its editing techniques. At the thematic level, Stone’s equation of the cultural and the biological taps into modern currents of reflection on violence proposed by theorists such as Michel Foucault (1975) and Yves Michaud (2002). At the narrative level, Stone’s killers are expelled like diseased bodies, consigned to the highways and back roads configuring the synaptic space between the fixed cultural centre that rejects them and the two emphatically mobile cultures that allow their malignancy to metastasize: an American frontier culture of human cast-offs and native nomads defined by the locomotion of the car, truck, trailer or caravan (Rapping 1999); and an international media culture that disseminates their image to the remotest corners of the globe. Finally, at the levels of cinematography and editing, an ethical question is asked with reference to the work of Baudrillard (1995): could the pathological “locomotion” prevailing in Stone’s narrative be read in tandem with a cinematic “media-motion” that is equally pathological and violent? Does Natural Born Killers draw the spectator into a flux of images and sounds that is artfully constructed to offend, to induce sickness? Can a flux of images and sounds be pathological, violent or criminal?